Growing incidence of thyroid carcinoma in recent years: Factors underlying overdiagnosis. Issue 4 (5th December 2017) - Sanabria, Alvaro; Kowalski, Luiz P.; Shah, Jatin P.; Nixon, Iain J.; Angelos, Peter; Williams, Michelle D.; Rinaldo, Alessandra; Ferlito, Alfio
Abstract: There is an increasing incidence of well‐differentiated thyroid cancer worldwide. Much of the increase is secondary to increased detection of small, low‐risk tumors, with questionable clinical significance. This review addresses the factors that contribute to the increasing incidence and considers environmental, and patient‐based and clinician‐led influences. Articles addressing the causes of the increased incidence were critically reviewed. A complex interplay of environmental, medical, and social pressures has resulted in increased awareness of the thyroid disease risk, increased screening of thyroid cancers, and increased diagnosis of thyroid cancers. Although there is evidence to suggest that the true disease incidence may be changing slightly, most of the increase is related to factors that promote early diagnosis of low‐risk lesions, which is resulting in a significant phenomenon of overdiagnosis. An improved understanding of these pressures at a global level will enable healthcare policymakers to react appropriately to this challenge in the future.